Women's experiences of antenatal transfer for threatened premature labour in NSW: A qualitative study. Issue 6 (November 2020) - Lewis, Melanie; Passant, Lynette; Cooke, Helen; Challis, Daniel
Abstract: Background: Each year thousands of pregnant women experiencing threatened premature labour are transferred considerable distances across Australia to access higher level facilities but only a small proportion of these women go on to actually give birth to a premature baby. Women from regional areas are required to move away from their home, children and support networks because of a perceived risk of birthing in a centre without neonatal intensive care facilities. Aim: This study examines the experience of women undergoing antenatal transfer for threatened premature labour in New South Wales and the Australian Capital Territory who do not give birth during their transfer admission. Methods: Thirteen semi-structured in-depth interviews were held with women across five tertiary referral sites across New South Wales and the Australian Capital Territory, and analysed until saturation for themes. Findings: Seven urban and six rural women were interviewed. Women and their families were all negatively affected by antenatal transfer. Factors that helped enable a positive experience were; enhanced sense of safety in the tertiary unit, and individual qualities of staff. Factors that contributed to negative experiences were; inadequate and conflicting information, and no involvement or choice in the clinical decision-making process to move to another facility. Conclusions: Antenatal transfer is an extremely stressful experience for women and their families. The provision of high quality written and verbal information, and the inclusion of women's perception of risk in the clinical decision making process will improve the experience for women and their families in NSW and the ACT.